THE INFLUENCE OF WORK FAMILY CONFLICT AND WORK ENVIRONMENT ON JOB SATISFACTION THROUGH JOB STRESS AS INTERVENING VARIABLES - Novalien Carolina Lewaherilla; Zakki Galib; Joko Rizkie Widokarti (Jurnal Ekonomi, 2023)
This study aims to analyze the effect of the relationship between Work Family Conflict and Work Environment on Job Satisfaction with Job Stress as an intervening variable during the 2020 pandemic for nurses at RSUD Dr. M. Haulussy Ambon. The research design used data analysis methods using the path paradigm with data analysis techniques using PLS-Path Modeling with the SMART PLS 3 application. The population used in this study were female nurses who were married at Haulussy Ambon Hospital with a total sample of 139 people. found from this study that Work Family Conflict has a significant positive effect on Job Stress, the Work Environment has a significant positive effect on Job Satisfaction,